2001
DOI: 10.1097/00042192-200109000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of whole soy foods results in significant reductions in clinical risk factors for osteoporosis and cardiovascular disease in normal postmenopausal women

Abstract: Dietary inclusion of whole soy foods containing 60 mg/d of isoflavones results in significant serum levels of phytoestrogens and reductions in several key clinical risk factors for CVD and osteoporosis in normal postmenopausal women. Long-term, placebo-controlled clinical trials are needed to evaluate the effect of phytoestrogens on the clinical endpoints of CVD and osteoporosis in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
1
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 34 publications
1
79
1
5
Order By: Relevance
“…In postmenopausal women, results of studies on isofl avone supplementation with various doses for 1.5 to 3 months were confl icting (Scambia et al 2000;Scheiber et al 2001;Uesugi et al 2002). In the present experiment, only a trend towards a higher osteoblastic activity was observed after 30 days IF daily consumption and resorption activity tended to decrease at d30 and to increase after 60 days of supplementation (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In postmenopausal women, results of studies on isofl avone supplementation with various doses for 1.5 to 3 months were confl icting (Scambia et al 2000;Scheiber et al 2001;Uesugi et al 2002). In the present experiment, only a trend towards a higher osteoblastic activity was observed after 30 days IF daily consumption and resorption activity tended to decrease at d30 and to increase after 60 days of supplementation (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The effects on bone markers are confl icting (Alekel et al 2000;Scheiber et al 2001). In fact, Setchell et al (2002) have hypothesised that intestinal metabolism of isofl avones could be the most important clue to the clinical effi cacy of soya foods in preventing osteopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones are one of the phytoestrogens that are possible preventive factors in several hormone-dependent cancers such as prostate cancer and breast cancer (Zhu et al, 2011;Khan et al, 2012 ), cardiovascular disease (Wong et al, 2012;Usui et al, 2013), menopausal symptoms (Aso et al, 2012;Jenks et al, 2012), and osteoporosis (Scheiber et al, 2001;Tousen et al, 2011). Especially, genistein and daidzein, which are aglycones of isoflavones, were found to have potential roles in the prevention of prostate cancer (Akaza et al, 2004;Nagata et al, 2007;Gardner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At the time, there was no recognition of a protective effect from isoflavones due to a paucity of data, but subsequent studies have shown that the cholesterollowering effect is influenced in a dose-dependent manner by the presence of isoflavones in the protein matrix [25,117]. Furthermore, data collected thus far in animals and from limited clinical trials show that isoflavones have protective or no effects on bone [8,29,62,93,100]. The synthetic phytoestrogen, ipriflavone, has been reported to increase the rate of bone formation (via a different mechanism than that of estradiol) where it may act analogous to SERMs having antiestrogenic effects on breast tissue, no apparent effect on uterotrophic activity and a proestrogenic effect on bone [8].…”
Section: Introductionmentioning
confidence: 99%